2007
DOI: 10.1890/06-0593
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Intertidal Food Webs by Avian Predators on New England Rocky Shores

Abstract: Although there is a large body of research on food webs in rocky intertidal communities, most of the emphasis has been on the marine benthic components. Effects of avian predation on highly mobile predators such as crabs, remains practically unstudied in rocky shore ecosystems. The crab, Cancer borealis, is an important component of the diet of gulls (Larus marinus, L. argentatus) at the Isles of Shoals, Maine, USA. C. borealis prey include the predatory gastropod Nucella lapillus L., the herbivore Littorina l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 49 publications
0
58
0
Order By: Relevance
“…For example, in a seagrass system, grazer richness had effects on system processes only with a predator present . Indeed, three manipulations of predator richness suggest that losing predator diversity from marine systems can have cascading effects on the algal communities (BYRNES et al, 2006;BRUNO and O'CONNOR, 2005;ELLIS et al, 2007). The results of these experiments parallel those of observational studies on functional diversity and predator extinctions.…”
Section: Roles Of Consumers and Interactions Among Trophic Levelsmentioning
confidence: 67%
“…For example, in a seagrass system, grazer richness had effects on system processes only with a predator present . Indeed, three manipulations of predator richness suggest that losing predator diversity from marine systems can have cascading effects on the algal communities (BYRNES et al, 2006;BRUNO and O'CONNOR, 2005;ELLIS et al, 2007). The results of these experiments parallel those of observational studies on functional diversity and predator extinctions.…”
Section: Roles Of Consumers and Interactions Among Trophic Levelsmentioning
confidence: 67%
“…Crabs can also have indirect effects on mussels through direct predation on other mussel consumers, such as whelks. Crab predation on grazers, such as Littorina littorea (Ellis et al 2007, Perez et al 2009, also has been shown to alter surface rugosity, and thus mussel recruitment, by effecting grazing activity (Petraitis 1990). In addition, ducks and gulls can have both direct and indirect effects on mussel v www.esajournals.org populations.…”
Section: Estuary Scale Differences In Consumer Pressurementioning
confidence: 99%
“…For example, gulls prey heavily on crabs in the Gulf of Maine, especially during summer months (Ellis et al 2005). By consuming crabs, gulls can have indirect trophic impacts on other invertebrates, including M. edulis as well as N. lapillus and L. littorea (Ellis et al 2007). Moreover, seasonal variation in bird predation on mussels (particularly by eiders) has been found to affect the size distribution of mussels remaining in a community, thereby affecting which consumers are most effective in subsequent mussel predation (Boudreau and Hamilton 2012).…”
Section: Estuary Scale Differences In Consumer Pressurementioning
confidence: 99%
“…Robles 1997, Posey et al 2006, Ellis et al 2007. In this experiment, we had multiple exclosure treatments involving different mesh sizes.…”
Section: Cage Effectsmentioning
confidence: 99%
“…In rocky intertidal communities, invertebrate (Paine 1966, Robles & Rob 1993, Navarrete & Menge 1996, Mowles et al 2011) and vertebrate (Hamilton 2000, Ellis et al 2007, Freudendahl et al 2010) predators can have important effects on community structure. Details of these effects are not always easy to identify in a field setting; species interactions can alter the overall effects of a species and complicate their measurement (Dungan 1986, Trussell et al 2003, Quinn et al 2012.…”
Section: Introductionmentioning
confidence: 99%